Effect of environmental enrichment for piglets in the nursery phase - Bortolanza Padilha-Boaretto, Joselaine; Groff-Urayama, Priscila Michelin [UNESP]; Einsfeld, Suelen Maria; De Souza, Cleverson; Mendes, Angélica Signor; Maeda, Emilyn Midori; Takahashi, Sabrina Endo (Asian Australasian Association of Animal Production Societies, 2021)
Objective: The effect of environmental enrichment on the behaviour of piglets in the nursery phase was evaluated. Methods: A total of 450 hybrid pigs (21 day old), including both females and uncastrated males, weighing approximately 6 kg, were distributed in a completely randomised design with 3 treatments and 3 replicates of 50 animals each. The treatments were: I) pen without environmental enrichment (control), ii) treatment consisting of continuous environmental enrichment (CEE) with rubber balls throughout the experimental period, and iii) treatment consisting of environmental enrichment with washed balls (EEWB) during the whole experimental period which were removed daily for washing. For the behavioural evaluation, 10 animals were randomly selected per replicate. The behavioural assessments were performed once a week, from 8 am to 6 pm, using images captured with a video camera. The data were submitted to non-parametric analyses, the means were compared using the Bonferroni test, and Person's correlations were also calculated. Results: A statistical difference (p = 0.001) was observed in the B5 (playful) behaviour; the animals in the EEWB treatment group had a higher frequency of this behaviour than animals in the control treatment group. The animals in the control group showed a higher frequency of B7 behaviour (lying down) (p = 0.026) than those in the EEWB and CEE treatment groups. The animals in the control group had a higher frequency of the B9 (belly nosing) behaviour than those in the EEWB group (p = 0.015). There was a tendency towards a higher frequency of behaviour B3 (walking in the pen) (p = 0.067) when the animals received the control treatment than treatments EEWB or CEE. Conclusion: The use of an enriching object improved the animal welfare and altered the correlation between the evaluated behaviours compared to the animals that did not have environmental enrichment.
Keywords: Animal Behaviour; Environmental Enrichment; Nursery Pig Breed; Welfare